A Simple but Accurate Estimation of Residual Energy for Reliable WSN Applications - Jae Ung Kim; Min Jae Kang; Jun Min Yi; Dong Kun Noh (International Journal of Distributed Sensor Networks)
A number of studies have been actively conducted to address limited energy resources in sensor systems over wireless sensor networks. Most of these studies are based on energy-aware schemes, which take advantage of the residual energy from the sensor system's own or neighboring nodes. However, existing sensor systems estimate residual energy based solely on voltage and current consumption, leading to inaccurate estimations because the residual energy in real batteries is affected by temperature and load. This misinformation makes a complete nonsense of existing energy-aware research, which is not allowed in reliable WSN applications. In this study, therefore, an efficient residual-energy estimation scheme is proposed in consideration of not only the voltage but also the temperature and load characteristics of batteries. The performance of the proposed scheme was verified through an experiment and simulations in the actual environment, and its effect gets more notable when the scale of the WSN goes larger.